The Transformational Leadership and Work Climate on Teacher Performance at Al-Azhar 56 Islamic School Malang: The Role of Work Motivation Mediation - Sulistiyaningsih, Tiyas; Suryani, Tatik (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of transformational leadership and work climate on teacher performance, with work motivation as a mediating variable at Al Azhar 56 Islamic School Malang. Using a quantitative approach and SEM-PLS analysis, data were collected from all teachers through questionnaires. Results reveal that both transformational leadership and work climate positively affect performance and motivation. Moreover, work motivation significantly mediates their effect on performance. These findings highlight the importance of inspirational leadership, a supportive work climate, and enhanced motivation in sustainably improving teacher performance in educational settings.